New strengthening mechanisms of nacre in the abalone shell. (2015) - Sullivan, MariAnne; Chen, Yan; Prorok, Bart
Abalone shells have been studied extensively because of their unique nacre structure. Colloquially known as mother-of-pearl, this material is surprisingly strong because of a biomineralised composite structure. There is a separate component of the structure that has not been well-addressed, termed as a mesolayer. These are found in wild abalones, and not typically in abalones from a farm-raised environment. Growth of the abalone shells was controlled in the laboratory setting in order to induce a change in structure with temperature fluctuations. The main goal was to induce a mesolayer with a temperature decrease, with the aim of replicating the shell architecture found in wild abalones. These findings will help shape new material architectures for protective applications.